Improving core instructional practice in mathematics teaching through lesson study. Issue 4 (9th October 2017) - Huang, Rongjin; Barlow, Angela T.; Haupt, Melanie E.
Abstract : Purpose: The purpose of this paper is to examine how teachers improve core instructional practices in teaching mathematics for problem solving through lesson study (LS). The core practices included launching a task, implementing a task, and orchestrating students' solutions. Design/methodology/approach: This study adopted multiple case study and survey methodologies. Each of three LS groups developed a research lesson on problem solving in algebra through Chinese LS, which includes collaborative planning and repeated teachings/debriefings of the research lesson with support from experts. The data collected included lesson plans, videotaped research lessons and debriefing meetings, and an end-of-project survey. Case studies supported by survey data were utilized to describe how research lessons were improved and what teachers learned from LS. Findings: A fine-grained analysis of the data revealed that the participants improved their strategies for teaching for problem solving, which included effectively launching tasks, strategically implementing tasks, and productively orchestrating students' solutions to the tasks. Further, analyses revealed that the feedback from experts during debriefing meetings played crucial roles in making these changes. Moreover, participants learned how to implement these core instructional practices and changed their views about students' learning. Originality/value: The study uncovers the mechanisms about how teachers improve teaching and their expertise in teaching through Chinese LS. The importance of the dynamic between repeated teaching and immediate feedback from knowledgeable others is highlighted.